Cephalosporins are the not the cause of death in a pregnant with urinary tract infection; A case Report: Cephalosporins and treatment of urinary tract infection during pregnancy - Jabarah, Mohammed Abdul- Hassan (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Urinary tract infection is a highly prevalent disease all over the world and affects females more than males. In the former, it may complicate pregnancy to potentially lethal septicaemia. Therefore, the aim of current case report was to show how misinterpretation of symptoms of septicaemia can lead to inadequate, and probably inappropriate, management with subsequent medico-legal consequences. Methods: A case study of a young pregnant female who developed urinary tract infection and treated with parenteral cephalosporins. The infection developed into septicaemia with subsequent miscarriage and death of the patient. Discussion: Misinterpretation of the symptoms of septicaemia resulted into delayed and inadequate management of the patient that resulted in death of the fetus, loss of consciousness of the patient and her death after that. Conclusion: Urinary tract infection during pregnancy may progress to septicaemia. Therefore, an early diagnosis and effective treatment may reduce potentially fatal outcomes.